2007
DOI: 10.1111/j.1745-4565.2007.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

INCIDENCE OF LISTERIA SPECIES IN SEAFOOD PRODUCTS OF MYSORE, INDIA

Abstract: Listeria monocytogenes is one of the most important foodborne pathogens causing illness in humans and animals. Thus, a study was undertaken to investigate the incidence of Listeria species in fresh and dry fish samples marketed in Mysore, India. A total of 164 fresh and dry fish samples collected from retail outlet shops of Mysore, South India, during the period August 2005 through August 2006 were examined for the presence of Listeria species by using ISO 11290 protocol. The incidence of Listeria species was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…The incidence of L. monocytogenes in our study was found to be 2.2% in fresh and frozen shrimp samples. These results are in agreement with reports by Masuda et al (1992) in Japan, Adesiyun et al (1993) in Trinidad, McLauchlin andNichols (1994) in England, Jinneman et al (1999) in the United States, and Moharem et al (2007) in India, where the bacteria were detected from 1.4%, 2.0%, 6.0%, 5.0% and 6.7% of fresh or frozen shrimp samples, respectively. However, higher contamination rates (10-53%) have also been reported (Jeyasekaran et al 1996;Cordano and Rocourt 2001;Ellner et al 1991;Minami et al 2010;Wan Norhana et al 2010).…”
Section: Dna Extraction and Pcr Conditionssupporting
confidence: 95%
See 1 more Smart Citation
“…The incidence of L. monocytogenes in our study was found to be 2.2% in fresh and frozen shrimp samples. These results are in agreement with reports by Masuda et al (1992) in Japan, Adesiyun et al (1993) in Trinidad, McLauchlin andNichols (1994) in England, Jinneman et al (1999) in the United States, and Moharem et al (2007) in India, where the bacteria were detected from 1.4%, 2.0%, 6.0%, 5.0% and 6.7% of fresh or frozen shrimp samples, respectively. However, higher contamination rates (10-53%) have also been reported (Jeyasekaran et al 1996;Cordano and Rocourt 2001;Ellner et al 1991;Minami et al 2010;Wan Norhana et al 2010).…”
Section: Dna Extraction and Pcr Conditionssupporting
confidence: 95%
“…In France, Ravomanana et al (1993) isolated Listeria in 23.5% of fresh shrimp samples. Manoj et al (1991), Dhanashree et al (2003), Moharem et al (2007) and Parihar et al (2008) detected Listeria spp. in 10.5%, 9.1%, 73.3% and 30.0% of fresh and frozen shrimp in India, respectively.…”
Section: Dna Extraction and Pcr Conditionsmentioning
confidence: 95%
“…From harvest to consumption, fish is easily contaminated by microorganisms that limit the shelf life of fishery products and because of this reason fresh fish is an extremely perishable food. During the course of storage, certain pathogens like Listeria monocytogenes, Vibrio parahemolyticus can grow from contaminated fish as well as from the processing environments [18]. The ban of chemical additives and antibiotic preservatives has driven the food research toward the search for natural antimicrobial compounds for food preservation.…”
Section: Introductionmentioning
confidence: 99%
“…In Iceland, Listeria was observed in 20.9% of the fresh shrimp studied (Gudmundsdottir and others ). However, several researchers (Dhanashree and others ; Moharem and others ; Jalali and Abedi ) did not observe L. monocytogenes in fresh shrimp samples. Although these products might contain L. monocytogenes , they do not pose a risk to the majority of consumers because they are generally cooked before consumption, similar to other aquatic food products.…”
Section: Prevalence Of L Monocytogenes In Water Aquatic Food Producmentioning
confidence: 94%